Private Sector’s Perceptions and Adoption of the E-invoicing System in Egypt - Soliman, Riham Mohamed (AUC Knowledge Fountain, 2024)
This study explores the private sector’s perceptions and adoption of the mandated e-invoicing system, a key component of Egypt’s digital tax system. Twenty-three qualitative semi-structured interviews with the private sector to answer the research question: How does the private sector perceive the mandatory e-invoicing system adopted by the Egyptian government? Furthermore, the study explored the perceived impact of the Unified Theory of Acceptance and Use of Technology (UTAUT)’s four aspects on the private sector’s perceptions and adoption of the system, including performance expectancy, effort expectancy, social influence, and facilitating conditions. The study’s findings show that all respondents confirmed the four aspects’ high influence in forming their perceptions, especially social influence and facilitating conditions. Moreover, the system’s acceptance level correlates positively with the enterprises’ size and financial resources, with larger enterprises adapting more effectively than micro, small, and medium enterprises (MSMEs). Performance expectancy concerns stem from user control, time-saving aspects, and financial implications. Effort expectancy issues are due to technical errors and lack of system integration. Social influence concerns include the system's limited geographic and sectoral coverage, fast-paced implementation process, absence of digital culture, and resistance to change. The facilitating conditions are critiqued for the system’s inadequate infrastructure, fears of security and data protection mechanisms, public servants’ insufficient digital capacity, and the government’s linear communication. Despite the concerns, there is an optimistic outlook for the system. To achieve this, the study provides policy recommendations to bridge the gap between the public and private sectors and enhance the system’s quality of services.